Review of the Banach-Stone Theorem - Bhatt, Biseswar Prasad (Journal of Development Review, 2023)
This is a quick overview of the isomorphism between spaces of continuous functions, or C(X) type spaces, that depend on compact Hausdorff spaces outfitted with the uniform norm. When two compact metric spaces, X and Y, are homeomorphic, Banach assumed the problem in 1932. He came to the conclusion that if C(X) and C(Y) are isometric isomorphic, then X and Y are homeomorphic. Stone then generalized this outcome for a general compact Hausdorff space in 1937. Then it is frequently referred to as the Banach-Stone theorem. There are numerous variations of this classic result. We can derive the topological features of X and Y from Gelfand and Kolmogoroff's algebraic version, which was published in 1939.